2011
DOI: 10.1371/journal.pone.0027584
|View full text |Cite
|
Sign up to set email alerts
|

Modern and Ancestral Genotypes of Mycobacterium tuberculosis from Andhra Pradesh, India

Abstract: Traditionally, the distribution of the Mycobacterium tuberculosis genotypes in India has been characterized by widespread prevalence of ancestral lineages (TbD1+ strains and variants) in the south and the modern forms (TbD1− CAS and variants) predominating in the north of India. The pattern was, however, not clearly known in the south-central region such as Hyderabad and the rest of the state of Andhra Pradesh where the prevalence of both tuberculosis (TB) and human immunodeficiency virus (HIV) infection is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 20 publications
2
38
1
Order By: Relevance
“…This supports the concept of clear demarcation between the strains prevalent in North and South India. This common finding is slightly different from the experience of Thomas et al [9] from Andhra Pradesh, who reported a higher prevalence rate of 40% for CAS type. This could be perhaps due to the presence of Non-Resident Indians (NRI) from Hyderabad who work in Middle East countries and migrant population from North Indian states who come and work in Hyderabad, which is the commercial capital of Andhra Pradesh state.…”
Section: Antibiotic Susceptibility Of M Tuberculosis From Eptb Specicontrasting
confidence: 96%
See 3 more Smart Citations
“…This supports the concept of clear demarcation between the strains prevalent in North and South India. This common finding is slightly different from the experience of Thomas et al [9] from Andhra Pradesh, who reported a higher prevalence rate of 40% for CAS type. This could be perhaps due to the presence of Non-Resident Indians (NRI) from Hyderabad who work in Middle East countries and migrant population from North Indian states who come and work in Hyderabad, which is the commercial capital of Andhra Pradesh state.…”
Section: Antibiotic Susceptibility Of M Tuberculosis From Eptb Specicontrasting
confidence: 96%
“…It was also pointed out from earlier studies that Beijing strains were absent in rural areas of Andhra Pradesh and rural TB units of Mumbai, though it was prevalent at a rate 6.8% in urban population of Andhra Pradesh, 10.4% among treatment failure cases and 3.4% from new cases of urban Mumbai. [9,10] As far as Manu strains are concerned, studies conducted in North India by various researchers have reported varying prevalence of these strains at a frequency of 1.2%, [7] 0.55% [11] and even 0% [5] in particular areas. Central India [8] has not recorded these strains.…”
Section: Research Work Conducted In Kerala and Chennaimentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with Beijing strains, EAI strains showed not only less virulence but also a 100-fold lower replication level in lung infections (33). It is noteworthy that the Manu and EAI lineages are believed to be closely related or even derived from a latest common ancestor (34). Although a small number of resistant strains might not be detected by molecular methods because of the overgrowth of sensitive strains in drug-free medium, a majority of resistant strains in cases of mixed infections can be detected in drug selection medium.…”
Section: Discussionmentioning
confidence: 97%